Comparison of Injury Epidemiology Between the Wenchuan and Lushan Earthquakes in Sichuan, China. (17th December 2014) - Hu, Yang; Zheng, Xi; Yuan, Yong; Pu, Qiang; Liu, Lunxu; Zhao, Yongfan
Abstract: Objective: We aimed to compare injury characteristics and the timing of admissions and surgeries in the Wenchuan earthquake in 2008 and the Lushan earthquake in 2013. Methods: We retrospectively compared the admission and operating times and injury profiles of patients admitted to our medical center during both earthquakes. We also explored the relationship between seismic intensity and injury type. Results: The time from earthquake onset to the peak in patient admissions and surgeries differed between the 2 earthquakes. In the Wenchuan earthquake, injuries due to being struck by objects or being buried were more frequent than other types of injuries, and more patients suffered injuries of the extremities than thoracic injuries or brain trauma. In the Lushan earthquake, falls were the most common injury, and more patients suffered thoracic trauma or brain injuries. The types of injury seemed to vary with seismic intensity, whereas the anatomical location of the injury did not. Conclusions: Greater seismic intensity of an earthquake is associated with longer delay between the event and the peak in patient admissions and surgeries, higher frequencies of injuries due to being struck or buried, and lower frequencies of injuries due to falls and injuries to the chest and brain. These insights may prove useful for planning rescue interventions in trauma centers near the epicenter. ( Disaster Med Public Health Preparedness . 2014;8:541-547)